Long-run effects of training programs for the unemployed in East Germany - Bernd Fitzenberger; Robert Völter (Institute for the Study of Labor (IZA), 2007)
Public sector sponsored training was implemented at a large scale during the transition process in East Germany. Based on new administrative data, we estimate the differential effects of three different programs for East Germany during the transition process. We apply a dynamic multiple treatment approach using matching based on inflows into unemployment. We find positive medium- and long-run employment effects for the largest program, Provision of Specific Professional Skills and Techniques. In contrast, the programs practice firms and retraining show no consistent positive employment effects. Furthermore, no program results in a reduction of benefit recipiency and the effects are quite similar for females and males.
urn:nbn:de:101:1-20080416344
Keywords: 330; Arbeitsmarktpolitik; Berufsbildung; Weiterbildung; Wirkungsanalyse; Beschäftigungseffekt; Neue Bundesländer